أشكال التفاعلية في الصحافة الإلكترونية الجزائرية وعلاقتها برضا المستخدمين: صحيفة كل شئ عن الجزائر TSA أنموذجاً - دراسة تحليلية وميدانية - بن معزوز، حميدة; بن طلبة، محمد البشير Bin Tulbah, Mohammed Albashir (جامعة الأمير عبد القادر للعلوم الإسلامية - كلية أصول الدين, 2019)
This study aims at revealing the various forms of interaction offered by the Algerian newspaper "All about Algeria TSA" and the satisfaction of its users with these interactive forms available. This study is based on the descriptive survey methodology. Using the content analysis tool, the questionnaire and the observation to participate as data collection tools, the following results were obtained: • TSA provided a variety of interactive digital windows, and the results of the analysis reflected the satisfaction of its users on these windows, with a satisfied category (48.68%). • With regard to the interactive media used, we find that they are available in a remarkable manner, especially the video archive, which satisfied the users of the newspaper, with a satisfied category (66.67%). Most users suggest adding an article (44.19%)
تهدف هذه الدراسة إلى الكشف عن مختلف أشكال التفاعلية التي تتيحها الصحيفة الإلكترونية الجزائرية كل شيء عن الجزائر TSA ، ومدى رضا مستخدميها بهذه الأشكال التفاعلية المتوافرة. وتعتمد هذه الدراسة على منهج المسح الوصفي، وباستعمال أداة تحليل المضمون، الاستبيان والملاحظة بالمشاركة كأدوات لجمع البيانات، تم التوصل إلى النتائج التالية : • وفرت صحيفة كل شيء عن الجزائر TSA نوافذ رقمية تفاعلية متنوعة، وقد عكست نتائج التحليل مدى رضا مستخدميها على هذه النوافذ، حيث حازت فئة راض نسبة (48.68%). • أما بخصوص الوسائط المتعددة التفاعلية المستخدمة، فنجد أنها متوافرة بشكل ملفت، خاصة أرشيف الفيديوهات الذي أرضى مستخدمي الصحيفة، حيث حازت فئة راض نسبة (66.67%). • نجد أن معظم المستخدمين يقترحون إمكانية إضافة مقال وبنسبة (44.19%)
Keywords: الصحافة الإلكترونية -- التفاعلية -- رضا المستخدمين -- تكنولوجيا الإعلام والاتصال -- الصحف الجزائرية -- صحيفة كل شئ عن الجزائر